Early clinical experience with Cascade: a novel temporary neck bridging device for embolization of intracranial aneurysms. (21st September 2019) - Sirakov, Stanimir; Sirakov, Alexander; Minkin, Krasimir; Karakostov, Vasil; Raychev, Radoslav
Abstract : Background: Temporary placement of a retrievable neck bridging device, allowing parent vessel flow, is an attractive alternative to balloon remodeling for treatment of ruptured intracranial aneurysms. Objective: To present, in a single-center study, our initial experience with Cascade (Perflow, Israel) in the treatment of ruptured intracranial aneurysms. Methods: During a period of 1.5 months, 12 patients with aneurysmal subarachnoid hemorrhage underwent coil embolization in conjunction with Cascade in our center. Retrospective analysis of prospectively collected angiographic and clinical data was conducted to assess the safety and efficacy of the device. Results: Among all treated patients, 41.7% (5/12) were female, the median age was 55 (47–77) years, the median aneurysm dome size was 5.75 mm (3–9.1), and the median neck size was 3.55 mm (2.3–7.9). Complete obliteration (Raymond 1) was achieved in 75% (9/12) of cases, and intentional residual neck (Raymond 2) was left in three cases (25%). None of the patients received any oral or intravenous antiplatelet therapy perioperatively. No thromboembolic complications, device-related spasm, vessel perforation, or coil entanglement were detected in any of the treated patients. Conclusions: In our initial experience, treatment of wide-neck ruptured intracranial aneurysms with Cascade is safe and effective, without the need for adjuvant antiplatelet therapy. Long-term follow-up data in larger cohorts are needed to confirm these preliminary findings.